Faktor – Faktor yang Berhubungan demgan Pemberian Makanan Tambahan (PMT) pada Bayi Usia (0-6) Bulan di Wilayah Kerja Puskesmas Garuda Kelurahan Tangkerang Tengah Kota Pekanbaru - Meliza Rasyid (Jurnal Kesehatan Komunitas, 2017)
Supplementary Feeding (PMT) in infants is the provision of food or beverages containing nutrients to infants or children aged 6-24 months to meet the nutritional needs after exclusive breastfeeding. Achievement rates of exclusive breastfeeding in Riau Province in 2011 was 45.9%, in 2012 increased to 46.2%. Exclusive breastfeeding PHC coverage in 2012 amounted to 60.4%, in 2013 decreased to 32.5%. The aim of research to determine the factors Associated with supplementary feeding (PMT) in infants aged (0-6) months in Puskesmas Garuda Village Middle Tangkerang Pekanbaru.This study is a quantitative analytical observational design (cross-sectional). With the dependent variable supplemetary feeding (PMT) and independent variables (education, employment, knowledge, and resources). The population in this study are all mothers who had infants aged (0-6) months, as many as 388 people with a partial sample of mother who had infants age (0-6) months as many as 128. The sampling technique is quota sampling. Data types consist of primay data and secondary data. Collecting primary data obtained directly from observations in the field through interviews with a quetionnaire measuring tool. The analysis which is used is the analysis of univariate, bivariate with Chi-square and multivariate. The results showed there is a relationship between education and the Feeding (P value 0.032, POR 95% CI = 2.338 1.137 to 4.808), knowledge (P value 0.002, POR value = 3.844 95% CI 1.710 to 8.639. )Is expected to relevant agencies to improve communication program, information, and education (KIE). establish cooperation across programs and sectors, more active in providing information to mothers with infants aged (0-6) months to education dan knowledge of the low one through the extension of the supplementary feeding (PMT). Keyword : supplementary feeding, education , knowledge,